A Contrastive Study on Lexical Bundles in English Debating by Chinese and American Debaters Based on SPSS Software - Limin Han, Aiyun Chen, Rongjie Zhai (Forest Chemicals Review, 1970)
Based on two self-built corpuses of English debating speeches, a contrastive study on lexical bundles used by Chinese and American debaters was conducted, by applying software Concapp and SPSS. Firstly, through software Concapp, lexical bundles (connectors and exemplifiers) in the two corpuses were searched on the basis of encoding them by CLAWS－－an automatic encoding software. Then, by adopting software SPSS, the mathematical and statistical analysis of using connectors and exemplifiers was carried out from two perspectives: density and richness degree. It was discovered that: the density and richness degree of connectors used by Chinese debaters was lower than that of connectors used by American debaters; the density and richness degree of exemplifiers used by Chinese debaters was higher than that of exemplifiers used by American counterparts. It was hoped that the research could provide some pedagogical implication and guidance on debate teaching practice.